Editorial: Affirmation? How to Learn to Live with ‘The Others’ Through Design - Enrique Nieto Fernández; Ester Gisbert Alemany (Diseña)
We approach design practices as practices of re-composition that ‘design’ encounters between entities with lives, interests, risks, materialities, politics, scales, and temporalities that are highly heterogeneous. This proposal draws attention to the responsibility of design in a world marked by an increasing ecosocial crisis, which demands not so much an improvement in our ability to design for others, but rather to live with others ‘through’ design. We will meet with disobedient ants, cultural management, invasive plants, ancestral knowledges, unstable amphibians, women’s communities, changing climates, Indigenous peoples, environments, and publics that—all together—design a ‘we’ that is always in formation, affecting the places where we work, the studios where we design, the classrooms where we learn, or the epistemologies from which we articulate our relationship with otherness.